A review on risk assessment in managed aquifer recharge. (23rd February 2022) - Imig, Anne; Szabó, Zsóka; Halytsia, Olha; Vrachioli, Maria; Kleinert, Verena; Rein, Arno
Abstract: Managed aquifer recharge (MAR) refers to a suite of methods that is increasingly being applied worldwide for sustainable groundwater management to tackle drinking or irrigation water shortage or to restore and maintain groundwater ecosystems. The potential for MAR is far from being exhausted, not only due to geological and hydrogeological conditions or technical and economic feasibility but also due to its lack of acceptance by the public and policymakers. One approach to enable the safe and accepted use of MAR could be to provide comprehensive risk management, including the identification, analysis, and evaluation of potential risks related to MAR. This article reviews current MAR risk assessment methodologies and guidelines and summarizes possible hazards and related processes. It may help planners and operators select the appropriate MAR risk assessment approaches and support the risk identification process. In addition to risk assessment (and subsequent risk treatment) related to the MAR implementation phase, this review also addresses risk assessment for MAR operation. We also highlight the limitations and lessons learned from the application and development of risk assessment methodologies. Moreover, developments are recommended in the area of MAR‐related risk assessment methodologies and regulation. Depending on data availability, collected methodologies may be applicable for MAR sites worldwide. Integr Environ Assess Manag 2022;18:1513–1529. © 2022 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC). Key Points: The past two decades have seen a marked increase in the literature on MAR‐related risk assessment, and a further increase is expected, since more attractive strategies are being used worldwide for integrated groundwater management. The development of holistic risk management plans can improve social acceptability and contribute to safer implementation and operation of MAR schemes. In connection with holistic risk management, MAR can be seen as a viable option for reaching the United Nations Sustainable Development Goal #6. Widely lacking regulations worldwide for risk assessment of MAR schemes is identified to hinder MAR implementation and safe operation worldwide.